Cost‐effectiveness of intravenous acetaminophen and ketorolac in adolescents undergoing idiopathic scoliosis surgery. Issue 3 (29th January 2018) - Chidambaran, Vidya; Subramanyam, Rajeev; Ding, Lili; Sadhasivam, Senthilkumar; Geisler, Kristie; Stubbeman, Bobbie; Sturm, Peter; Jain, Viral; Eckman, Mark H.
Summary: Background: Enhanced recovery after surgery protocols increasingly use multimodal analgesia after major surgeries with intravenous acetaminophen and ketorolac, despite no documented cost‐effectiveness of these strategies. Aims: The goal of this prospective cohort study was to model cost‐effectiveness of adding acetaminophen or acetaminophen + ketorolac to opioids for postoperative outcomes in children having scoliosis surgery. Methods: Of 106 postsurgical children, 36 received only opioids, 26 received intravenous acetaminophen, and 44 received acetaminophen + ketorolac as analgesia adjuncts. Costs were calculated in 2015 US . Decision analytic model was constructed with Decision Maker ® software. Base‐case and sensitivity analyses were performed with effectiveness defined as avoidance of opioid adverse effects. Results: The groups were comparable demographically. Compared with opioids‐only strategy, subjects in the intravenous acetaminophen + ketorolac strategy consumed less opioids ( P = .002; difference in mean morphine consumption on postoperative days 1 and 2 was −0.44 mg/kg (95% CI −0.72 to −0.16); tolerated meals earlier ( P < .001; RR 0.250 (0.112‐0.556)) and had less constipation ( P < .001; RR 0.226 (0.094‐0.546)). Base‐case analysis showed that of the 3 strategies, use of opioids alone is both most costly and least effective, opioids + intravenous acetaminophen is intermediate in both cost and effectiveness; and opioids + intravenous acetaminophen and ketorolac is the least expensive and most effective strategy. The addition of intravenous acetaminophen with or without ketorolac to an opioid‐only strategy saves 510‐947 per patient undergoing spine surgery and decreases opioid side effects. Conclusion: Intravenous acetaminophen with or without ketorolac reduced opioid consumption, opioid‐related adverse effects, length of stay, and thereby cost of care following idiopathic scoliosis in adolescents compared with opioids‐alone postoperative analgesia strategy.